A CORRELATIVE STUDY BETWEEN STUDENTS’ ACHIEVEMENT IN ENGLISH DEBATE AND THEIR WRITING ARGUMENTATIVE ESSAY - Riastanti, Restiana Erma (Pusat Pengembangan Bahasa IAIN Tulungagung, 2014)
Arguing has been existing in our daily life as we do this all the time with a simple argumentation as well as the most complicated one. One of the activity in pedagogy field, especially in learning second or foreign language, having debate activity might be done as the way in enhancing students? ability in speaking particularly in arguing. Besides that, debate activity is beneficial for L2 learners in improving another ability for instance their ability in listening. However, not only are arguments delivered through a spoken way, but it also could be delivered in the written one. This way can be reached by making an argumentative essay. They?re obviously have some similarities in term of not only the contents but also the process in setting up the arguments. In accordance, this paper presents whether or not students? achievement in debating correlates to their achievement in writing argumentative essay. However, the result was not as like as what it had been expected. As, the coefficient correlation was classified into a very low correlation. The discussion about the possible reason of why this could happen was also included in the last part.